2000
DOI: 10.3346/jkms.2000.15.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor in malignant and tuberculous pleural effusions

Abstract: The purpose of this study is to assess the usefulness of soluble vascular endothelial growth factor (VEGF) in the effusions of patients with malignant and tuberculous diseases. Using a sandwich enzyme-linked immunoadsorbent assay, VEGF concentration was measured in malignant (n=17) and tuberculous (n=11) pleural effusions. Pleural biopsy, cytology or microbiological methods were used to make final diagnoses. Adenosine deaminase (ADA) levels in tuberculous pleural effusions were significantly higher than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 0 publications
3
19
0
3
Order By: Relevance
“…No significant differences were observed in pVEGF-A levels between lung and gastric cancer patients, which is consistent with other studies that observed no significant difference in supernatant fluid VEGF-A levels in patients with different histological types or clinical stages of lung cancers (12,23). Multiple linear regression analysis was used to demonstrate that the levels of VEGF-A in the supernatant fluid of the patients with bloody effusion were increased compared with the patients with non-bloody effusion, which is consistent with other previous studies that demonstrated that the pleural VEGF-A level is associated with the number of red blood cells (14,24,25).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…No significant differences were observed in pVEGF-A levels between lung and gastric cancer patients, which is consistent with other studies that observed no significant difference in supernatant fluid VEGF-A levels in patients with different histological types or clinical stages of lung cancers (12,23). Multiple linear regression analysis was used to demonstrate that the levels of VEGF-A in the supernatant fluid of the patients with bloody effusion were increased compared with the patients with non-bloody effusion, which is consistent with other previous studies that demonstrated that the pleural VEGF-A level is associated with the number of red blood cells (14,24,25).…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have demonstrated that VEGF-A protein is present in significant amounts in peritoneal and pleural effusions of varying etiologies (9,10). VEGF-A levels in malignant effusions were found to be significantly increased compared with those in non-malignant effusions, indicating that this difference may aid in the differentiation between malignant and non-malignant effusions (11,12). The altered expression of VEGF-A has been reported to be associated with the poor prognosis of various types of human cancer (13,14).…”
Section: Introductionmentioning
confidence: 98%
“…Our study is in accordance with these previous data, showing an increased level of VEGF in malignant effusion. Lim et al compared VEGF levels of tuberculous PE (median, 994 pg/ dl) and malignant PE (2418 pg/ dl), reaching to similar results obtained in our study [20]. In our series, VEGF of PE levels in empyema patients were higher than other nonmalignant groups (p = 0.02).…”
Section: Discussionsupporting
confidence: 78%
“…Following independent review, 181 publications concerning VEGF and pleural effusions were considered to be eligible for inclusion in the analysis. Of these publications, 144 were excluded for being beyond the scope of the present study, one was excluded due to the lack of a control group (9), two letters to the editor were excluded due to the limited data they contained (21,22), four publications were excluded as they recruited <10 patients in one of study groups (10,11,14,23) and 20 were excluded as they did not allow data extraction or calculation of the sensitivity and specificity (12,13,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). The remaining 10 studies, based on 514 patients with MPE and 511 without MPE, were available for the meta-analysis (42-51).…”
Section: Resultsmentioning
confidence: 99%
“…VEGF is pivotal in the formation of MPE, as it increases vascular permeability and vascular leakage of fluid (9,10). In addition, a high level of pleural VEGF has been found to be correlated with malignancy (11) and thus an increasing number of studies consider VEGF to be a marker for the diagnosis of MPE (12)(13)(14). However, conflicting results have been reported and the exact role of VEGF remains unclear.…”
Section: Introductionmentioning
confidence: 94%